ANALYSIS OF CLASSROOM MANAGEMENT STRATEGIES IN INCREASING STUDENTS’ LEARNING MOTIVATION IN ENGLISH AT SMP NEGERI 3 GUNUNGSITOLI ALO’OA - Zega, Revordika; Maru'ao, Nurasayani; Harefa, Trisman; Laoli, Adieli (Esteem Journal of English Education Study Programme, 2025)
This study aims to analyze the classroom management strategies applied by the English teachers in the eighth grade at SMP Negeri 3 Gunungsitoli Alo'oa in increasing student learning motivation, as well as to assess the outcomes of these strategies. The research method employed is qualitative with a descriptive methodology, involving data collection techniques such as observation, interviews, and documentation. The findings indicate that the classroom management strategies applied including seating arrangements, varied teaching methods, and the provision of positive feedback significantly contribute to enhancing student learning motivation. Appropriate physical classroom arrangements that align with student characteristics, along with the use of diverse teaching methods such as group discussions and give praise, have proven effective in maintaining student engagement and interest. The implications of this study emphasize the importance of structured classroom management, flexibility in teaching methods, and the application of positive feedback in creating a supportive learning environment that boosts student motivation. These findings support theories regarding the influence of classroom design, varied teaching techniques, and positive feedback on student learning outcomes.